Report of the address at the opening of the fifth session of the Dublin Statistical Society - Kane, Robert, Sir (Statistical and Social Inquiry Society of Ireland, 1851)
Honoured by the request of the council of this society that I should, as acting vice-president, open the business of this its fifth session with such observations as might serve to supplement the annual report which has been laid before our members, and should afford same explanation to our visitors as to the objects of the society, and the progress we have as yet made, I hasten to comply with the duties of a position in which my personal and legitimate appreciation of the honour conferred upon me does not blind me to its difficulties, or prevent me sincerely wishing that the cause of the society, and of the important departments of science which are its care, had been intrusted by the council to some more able advocate.
Read November 19th 1851
Keywords: Statistical methods; 314.15